Becoming a researcher. (21st August 2012) - Flood, Samantha; Bennett, Davey; Melsome, Melissa; Northway, Ruth
Abstract : Accessible summary: This paper is about three people with learning disabilities. They work as co‐researchers. They have written this paper with support. Support is important to them. It has helped them to do the research. They each have a personal assistant. Other people working on the project also help them. They have had training and practised what they needed to do before asking other people questions. They have learnt a lot of new skills and have made a lot of decisions about the project. They enjoy their work and hope that other people will learn from their stories. They hope that other people with learning disabilities will want to do research. Summary: People with learning disabilities are increasingly taking on the role of researcher within participatory research projects. This paper talks about what it means to be a researcher using the words, views and experiences of three people with learning disabilities who are currently working as co‐researchers. It talks about what they have found helpful, and what they have found challenging. It compares their experiences to those of other people and highlights the importance of support. Overall they report that it has been a positive experience which has helped them to learn a great deal and they provide advice that they hope will help others thinking about taking on such a role.